English Speaking Difficulties Encountered by The Islamic Boarding School Students Daarul Mughni Bogor - Supeno Supeno; Imam Suseno; Kokok Purwanto (Deiksis, 2021)
The research is to find out the students’ speaking difficulties encountered by Islamic Boarding School Daarul Mughni Bogor, Indonesia. The research objective identifies and describes the process result of the students’ observation, questionnaire, and interview related to linguistic factors, non-linguistic factors, and both causes. The subject of this research is the students as about 80 respondents with a descriptive analysis of qualitative research. The research methodology is considered to be appropriately applied for the study of linguistic analysis and a description of the data. The population of the research study is the 12th – grade students of Daarul Mughni Islamic Boarding School Bogor, Indonesia. The sample of the research study was chosen by using a simple random sample of 80 respondents of 292 students. Descriptive research is selected by the researcher because it deals with the phenomenon of the students’ speaking difficulties in a real-life situation that happened to the students while they are speaking English at school. The description of the questionnaire result explains about three aspects such as linguistic factors, non- linguistic factors, and the causes of speaking difficulties related to the environment, speaking difficulties related to English teaching, and curriculum design